Bitch Planet. Book one, Extraordinary machine - DeConnick, Kelly Sue; DeConnick, Kelly Sue; De Landro, Valentine (Image Comics, 2015)
In a future just a few years down the road in the wrong direction, a woman's failure to comply with her patriarchal overlords will result in exile to the meanest penal planet in the galaxy. When the newest crop of fresh femmes arrive, can they work together to stay alive or will hidden agendas, crooked guards, and the deadliest sport on (or off!) Earth take them to their maker?